2010
DOI: 10.3109/10826084.2010.509853
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Experience and Later Onset of Illegal Drug Use Among African American Students on HBCU Campuses

Abstract: Few studies examine whether early sexual experience is associated with subsequent illegal drug use among adolescents. A sample of 7,372 African-American students who had not used illegal drugs before the age of 14 were identified in the dataset of the 2001 Historically Black Colleges and Universities (HBCU) Substance Use Survey. Using self-reported ages of onset, discrete-time survival models estimated the hazard of illegal drug use onset after age 13 subsequent to first sexual intercourse. Early sex was modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Participants reporting early sexual debut were more likely to report drug use associated with sexual activity, which is found in existing literature with regard to early initiation of sex (Bellis et al, 2008; Stanton, Li, Cottrell, & Kaljee et al, 2001; Wang, Storr, Browne, & Wagner, 2010). In a study developed in eight African countries with adolescents (Peltzer, 2010), for example, the authors reported a high prevalence of early sexual debut.…”
Section: Discussionsupporting
confidence: 54%
“…Participants reporting early sexual debut were more likely to report drug use associated with sexual activity, which is found in existing literature with regard to early initiation of sex (Bellis et al, 2008; Stanton, Li, Cottrell, & Kaljee et al, 2001; Wang, Storr, Browne, & Wagner, 2010). In a study developed in eight African countries with adolescents (Peltzer, 2010), for example, the authors reported a high prevalence of early sexual debut.…”
Section: Discussionsupporting
confidence: 54%
“…32 Women rated being under the influence of alcohol of drugs the highest barrier to engaging in safer sex. 10 …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the association of an early drug use debut and later risk behavior appears to be multidirectional, as subsequent risky substance use practices (e.g., needle sharing), sexual practices (e.g., multiple partners, transactional sex, lack of condom use), and substance use in general have all been linked. This crossover of risk behavior domains, thus, suggests that early initiation of either type of risk behavior can be associated with the other [ 6 , 24 , 25 , 27 , 31 , 37 , 49 , 63 – 65 , 76 , 78 80 , 89 , 98 , 103 , 104 ], and both might operate synergistically (e.g., drinking or illicit drug use coupled with unprotected sex [ 105 ]) as part of a tendency toward a generally riskier lifestyle.…”
Section: Discussionmentioning
confidence: 99%